2023
DOI: 10.1175/mwr-d-22-0026.1
|View full text |Cite
|
Sign up to set email alerts
|

Supercell-External Storms and Boundaries Acting as Catalysts for Tornadogenesis

Abstract: It has long been observed that interactions of a supercell with other storms or storm-scale boundaries sometimes seem to directly instigate tornadogenesis. First, the authors explore the frequency of such constructive interactions. WSR-88D radar data are used to categorize 136 tornadic supercells into isolated supercells and supercells that interacted with external factors within 20 min before tornadogenesis. Most cases (80%) showed some form of external influence prior to tornadogenesis. Common patterns of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…In high streamwise vorticity environments, the probability of tornadogenesis is argued to be high because very little (or no) augmentation from the storm is required in order to instigate the dynamical updraft response that favors tornadogenesis. On the other hand, in low streamwise vorticity environments, the probability of tornadogenesis is argued to be lower because much more augmentation from the storm is required (or from external sources such as storm mergers, e.g., Fischer and Dahl 2022a). The necessity of within-storm supplementation adds to the possible failure points, as there must be favorable storm interactions and/or sufficient dynamic lifting to overcome the negative buoyancy associated with the baroclinic vorticity generation.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In high streamwise vorticity environments, the probability of tornadogenesis is argued to be high because very little (or no) augmentation from the storm is required in order to instigate the dynamical updraft response that favors tornadogenesis. On the other hand, in low streamwise vorticity environments, the probability of tornadogenesis is argued to be lower because much more augmentation from the storm is required (or from external sources such as storm mergers, e.g., Fischer and Dahl 2022a). The necessity of within-storm supplementation adds to the possible failure points, as there must be favorable storm interactions and/or sufficient dynamic lifting to overcome the negative buoyancy associated with the baroclinic vorticity generation.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Because of the societal hazards associated with these storms, timely and accurate prediction is key. While the overall environmental conditions responsible for supercell formation are well known [2][3][4][5], many studies have found that gradients (or boundaries) in the mesoscale environment can have a substantial impact on the supercell structure and evolution [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%